Walleye Pollock breach the Bering Strait: A change of the cods in the arctic. (October 2022) - Wildes, Sharon; Whittle, Jackie; Nguyen, Hanhvan; Marsh, Maxwell; Karpan, Kirby; D'Amelio, Catherine; Dimond, Andrew; Cieciel, Kristin; De Robertis, Alex; Levine, Robert; Larson, Wes; Guyon, Jeff
Abstract: We used genetic techniques to identify gadids (cods) to species in the Pacific Arctic during a time of substantial physical change in the marine ecosystem between 2012 and 2019. The dominant fish species in the Chukchi Sea is Arctic Cod ( Boreogadus saida ); however, other gadids such as Saffron Cod ( Eleginus gracilis ), Pacific Cod ( Gadus macrocephalus ) and Walleye Pollock ( Gadus chalcogrammus ) have been observed. Two aims in this study were to evaluate the accuracy of at sea morphological identification (which can be difficult for juveniles) with genetic species identification and to document potential variation in species composition and distribution of gadids in the Pacific Arctic in response to changing environmental conditions. Microsatellite and mtDNA genetic results revealed that most B. saida collected in the Chukchi Sea in 2012 and 2013 were correctly identified at sea . Conversely, genetic results from samples collected in 2017 and 2019 revealed a large number of G. chalcogrammus and some G. macrocephalus and E. gracilis that were initially identified at sea as B. saida . The majority of misidentification occurred between B. saida and G. chalcogrammus . This study indicates a northward shift of G. chalcogrammus and B. saida during warmer conditions. In addition, juvenile Polar Cod ( A. glacialis ), which is not typically found in the Chukchi Sea and was not identified at sea, was genetically detected on 3 hauls on the northern Chukchi Shelf, outside of its documented distribution. Accurate species identification, especially during a time of changing marine landscapes, is not only important for survey abundance estimates but for downstream analyses as well. This emphasizes the value of implementing strategies for correct identification of the gadid species to better capture and monitor responses to varying and likely changing conditions. Our results provide strong evidence of distributional shifts and range expansions of gadid species in the Arctic, which may be the result of changing climactic conditions.